(untitled) (American Journal of Islam and Society, 1992)
The ongoing controversy over artificial and human intelligence is characterized by open disagreement. Some researchers believe that artificial intelligence has the potential to become equal to or even superior to human intelligence, while others say that such a development is impossible. The thesis of this paper is that the gap between human and artificial intelligence is bound to remain considerable, both in the short term and in the long term. The concepts of human cultural symbols and the Qur’anic vision of human intelligence are intduced in support of this thesis. Humanity’s ability to manipulate cultural symbols, upon which the phenomenon of human intelligence depends, is a uniquely human characteristic. And this uniqueness, according to the Qur’an, is the direct result of a divine decision, not of evolution. As such an ability and many of the mysteries of that power, are hardly accessible to humans, how would human researchers be able to include them in the design of artificial intelligence machines? In the last two decades, research in the field of artificial intelligence (hereinafter referred to as AI) has made considerable headway on both the theoretical and the applied levels. The input into the field has not been restricted only to cybernetics and information process experts; neurophysiologists, cognitive psychologists, philosophers, and sociologists’ have also been interested in human intelligence (hereinafter referred to as HI) and AI. As AI infrastructures and authority continue to expand in modem and postmodem societies, specialists in other areas will have to become involved. For scientists, basic and applied research into A1 constitute an exciting ...